STRATEGI PUBLIC RELATIONS DALAM MEMPERTAHANKAN CITRA TUJU TUJU COFFEE - Ovyanti, Sheyvandra; Andrini, Susi (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
This study aims to determine and analyze the Public Relations Strategy in Maintaining the Image of Tuju Tuju Coffee which is known as Palm Sugar Milk Coffee with a strong coffee flavor called ‘Kopi Yang DiTuju.’ This study uses a descriptive qualitative method with data collection of participant observation, in-depth interviews and documentation. The sources in this study consisted of key informants, namely the Owner and Public Relations of Tuju Tuju Coffee and three supporting informants, namely the barista of Tuju Tuju Coffee, a professional barista and loyal customers. Data analysis uses four concepts of Public Relations Strategy stages from (Cutlip, Center and Broom). The results of this study in the first phase, the image is formed through trust built by customers with the problem of how to maintain the image and consistency of the strong taste of Palm Sugar Milk Coffee - ‘Kopi Yang DiTuju. The second phase is planning and programming, namely by selecting quality coffee beans, looking for human resources (baristas), innovating and participating in events/exhibitions. In the third phase, taking action and communication, namely maintaining relationships with farmers, cooking coffee beans, baristas calibrating, innovating with mobile coffee carts and participating in coffee events to build relationships and public trust. The fourth phase evaluates the program, by providing assessments and implementations and the results of the programs that have been implemented. Thus, Tuju Tuju Coffee demonstrates that its brand image aligns with customer perceptions of consistent, strong-tasting palm sugar milk coffee.